The Existence and Education of Ceramic Craftsmen Society of Polutan Village in the 4.0 Industrial Revolution Era - Tupamahu, Maria Katje; Tupamahu, Kevin Hermanto; Rauf, Rose Amnah Abd; Mesra, Romi (IJECA (International Journal of Education and Curriculum Application), 2022)
This research is different from previous research where this research specifically wants to describe and reveal what the existence of the ceramic craftsman community is like, which incidentally is still a lot of people who use traditional methods in a modern era and its relationship with the level of education of the community where the people can get jobs from all age. The research method used in this study is a qualitative research method in which researchers seek data in the form of explanations from informants and other relevant data sources. The data collection method in this study used unstructured interview techniques and half-involved observation in order to obtain valid data and in accordance with the research objectives. Teknik penentuan sampel pada penelitian ini yaitu menggunakan snowball sampling. Researchers use data analysis with data reduction, data presentation, and finally drawing conclusions or verification. The results of the research are as follows: (1) There are no “unemployed” people of all age levels; (2) People Prefer to Work as Ceramic Craftsmen so that few continue their undergraduate education; (3) Pulutan Village is Known as a Tourism Village for Ceramic Craftsmen in Minahasa; (4) Pulutan Village Ceramic Industry Needs Government Support To Further Develop; and (5) Pulutan Village Is Often Used As A Place To Develop Knowledge And Skills. The implication of this research is for the development of science, especially the discipline of sociology related to rural sociology, sociology of tourism, and so on as well as social science in general. Conclusion of this research are we can see that Pulutan Village as one of the tourist villages due to their tradition as ceramics and grain craftsmen is a village. very independent even the unemployment rate is very low.